IMPLIKASI SOSIAL EKONOMI PONDOK PESANTREN TERHADAP EKONOMI MASYARAKAT: Studi di Pondok Modern Darussalam Gontor Putri di Kec. Mantingan, Kab. Ngawi, Jawa Timur - Fajari, Alfiani Bintang; Manzilati, Asfi (Islamic Economics and finance in Focus, 2023)
Humans are social creatures so each individual will always interact with one another in meeting their needs. This interaction has a socio-economic impact on other communities. Pondok Modern Darussalam Gontor Putri which is located in Mantingan also interacts with the community which has an impact on its surroundings. Therefore, this research wants to find out how to realize the social economy of Islamic boarding schools to the community's economy. The method used in this research is the case study method. The results of the study found that Islamic boarding schools also had an impact on the socio-economic community. The economic impact arising from the interaction between the community and the cottage is to create jobs and generate a desire to open businesses such as lodging, stalls, and laundries to meet the needs of migrants related to the cottage. Apart from that, the social relationship between Pondok and pesantren has more impact on education and the religious community with the dedication carried out by ustadz and ustadzah Gontor at the TPA and MI which were founded by Pondok Gontor. The relationship between Pondok Gontor and the community has also experienced several problems regarding Pondok's land being used by the community. In their settlement, they consult with each other and then settle it legally if there is no common ground for agreement